Case Report: Multiple gastrointestinal stromal tumors along with numerous cutaneous neurofibromas: a case description and literature analysis - Zhao, Congcan; Jin, Liquan; Tan, Yunbo; Chen, Yiming; Su, Ziting; Li, Wenwu; Yang, Qing (Frontiers in Oncology, 2023)
Multiple gastrointestinal stromal tumors (GISTs) combined with cutaneous multiple neurofibromas are clinically rare. This paper presents a case of multiple gastrointestinal stromal tumors in the jejunum of a 68-year-old mother, along with her daughter who also had coexisting cutaneous multiple neurofibromas. The mother had been experiencing repeated melena for over 2 years and had previously been diagnosed with multiple small intestinal masses at other hospitals. Additionally, her 42-year-old daughter was admitted to our department due to recurrent abdominal pain caused by cholecystolithiasis. The mother and daughter both exhibited multiple nodular masses of varying sizes on their skin, including the truncus, limbs, and face, which were diagnosed as neurofibromas. The mother underwent a partial excision of the jejunum and a lateral jejunojejunal anastomosis side-to-side, as well as excision of skin lesions in our department. The final diagnosis of wild-type GISTs associated with neurofibromatosis type 1 (NF1) was confirmed through postoperative pathology, immunohistochemistry, and genetic testing results. During preoperative gastrointestinal endoscopy and intraoperative laparoscopic exploration of the gastrointestinal tract, no obvious tumors were found in her daughter. A combination of patient observations and a review of relevant literature in the field suggests that when patients present with gastrointestinal symptoms and multiple irregular painless swellings in the skin, it is important to consider the possibility of an association with NF1 and GIST. Additionally, obtaining a detailed family history can save time and improve the diagnosis of patients with both NF1 and GIST. We recommend that even if there are no gastrointestinal manifestations of GISTs in the offspring of newly mutated NF1 patients, regular review of gastroenteroscopy, imaging examination, and long-term follow-up after middle age are still crucial for the early diagnosis and treatment of NF1-related GISTs.